Compare Chinese Corporate Governance with Anglo-American and German-Japanese Models - Wang, Wenhao (2006)
The corporate governance system in developed countries can be mainly distinguished into Anglo-American Model and German-Japanese Model. This paper attempts to analyze the characteristics of corporate governance in the UK, US, Germany and Japan, then compares them with corporate governance of contemporary China, and finally concludes the comparative characteristics of Chinese corporate governance.